Workflow para desenvolvimento de aplicações robóticas com requisitos de tempo real - Pinto, Matheus Leitzke (2020)
In robotic systems, in most cases, there is the need to meet the time constraints imposed by the design requirements. Thus, it is necessary the use of real-time systems (RTS). This kind of computational platform provides resources that guarantee temporal predictability, that is, that the time parameters related to their services can be determined at the design phase. This work presents a complete workflow, from the determination of the computational platform used as RTS, to the implementation of the application in an operational robot. In the evaluation of computational systems, a benchmark called Hart-ROS was developed, as the real-time performance analysis tool. After validating the RTS, a mobile robot application with time requirements was developed. The materials used to implement the robot are easy to find in brazilian and international market. Moreover, the methodologies are based on real-time literature and they are presented in-depth. As far we know, no work has systematically presented in stages the development of a robot that meets the timing requirements of an application, só that it can be replicable by a large part of the community. It can be seen that the proposed workflow is a fully open solution in the development of robots, in which it is possible to create an application that meets the timing requirements of the project, using the scientific body of knowledge as foundation.